مؤشرات تمويل ريادة الاعمال في الدول الاوروبية بأسلوب المركبات الاساسية (pca): باستخدام R - بركان, عماد; حرنان, نجوى (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة الى ابراز مؤشرات تمويل ريادة الاعمال في الدول الأوربية ، مع تعزيز كل المحددات . كان هدفنا من البحث هو تحديد المساهمين في تمويل ريادة الاعمال وتطوره داخل الدول الأوروبية من مجموعة من الابعاد هذا بتطبيق تحليل المكونات الرئيسية. اذ تم استخدام اربعة مؤشرات رئيسية. ووجد أن عاملين تفسر 84.62 % من مجموع التباين في البيانات ، وتشير النتائج إلى أن تمويل ريادة الاعمال خيار استراتيجي يمكن ممارسته لخلق ميزة تنافسية وتعزيز النمو الاقتصادي المستدام This study aimed the indicators of financing entrepreneurship in European countries, while strengthening all the determinants. Our aim of the research was to identify the contributors to the financing of entrepreneurship and its development within European countries from a set of dimensions, by applying the main components analysis. Four main indicators were used. It was found that two factors explain 84.62% of the total variance in the data, and the results indicate that financing entrepreneurship is a strategic option that can be exercised to create a competitive advantage and promote sustainable economic growth
Indicators of Financing Entrepreneurship In European Countries By The Principal Component Method (PCA): Using R
مقال
Keywords: leading businesses; basic compounds; entrepreneurship financing; European countries